Public Company: Corporate Governance in the Law of the Republic of Kazakhstan - Sara, Idrysheva; Tatyana, Klimova (International Journal of Psychosocial Rehabilitation, 2020)
We consider the institution of a “public company”, which existed in the legislation on joint-stock companies of the Republic of Kazakhstan from 2007 to mid-2018. A comparative legal analysis of the legislation and corporate practice of other countries in the article justifies the necessity of this legal institution for Kazakhstan. To justify maintaining the rules on public companies complying with the OECD principles is provided by the provisions of the Legal Policy Concept and the Address of the President of the Republic of Kazakhstan on strengthening the institution of “public corporations” and introducing the principles of corporate governance of the OECD. As a result of comparing the institution of public companies with other legal entities of public law in Kazakhstan, we come to the conclusion that the requirements for the latter are presented only in terms of observing the transparency of financial statements. Having considered by-laws of the Republic of Kazakhstan governing corporate relations in organizations with a predominant share of the state, it is concluded that the OECD principles are mandatory for all companies, regardless of ownership, and that the principles of corporate governance are not fixed at the level of by-laws, but at the level of laws.